Analysis of BPJS Health and Non-BPJS Health Patient Satisfaction on Inpatient Services at X Hospital - Andini, Rizkia Yuniar Nur; Nurfikri, Ari; Shanty, Janthi Dharma; Achmadi, Nanang Kurnia (International Journal of Nursing Information, 2023)
As a health insurance programme implemented by the government, the Social Security Administration for Health, or BPJS Health, often raises questions regarding the level of patient satisfaction in receiving health services. However, as a mandatory programme for all Indonesian citizens, the presence of BPJS Health affects the number of hospital visits due to the ease of financing treatment. The purpose of this study is to explain the relationship between patient satisfaction and the use of BPJS Health and to describe the perceptions of BPJS Health and non BPJS Health patients on the quality of inpatient services at Hospital X. The method used for this study is a quantitative approach with the research location at Hospital X in Depok City, West Java. There is no difference in the level of patient satisfaction between BPJS Health and non BPJS Health patients towards inpatient services. This article is expected to contribute to affirmation for hospitals in providing services that do not differentiate services for general patients, insurance, and BPJS Health.